MUNASABAH PASANGAN DIKSI AL-QURAN - Amri, Muhammad (Rausyan Fikr: Jurnal Ilmu Studi Ushuluddin dan Filsafat, 2018)
Attention to the Qur'anic word (mufradat al-Quran) is sufficient for a large portion of the Qur'anic Study. Whether in the form of detecting the correct selection of words in a verse, the study of repetition of words in the Qur'an, to the linkage of each word in a single verse of the Qur'an. It turns out that in the Qur'an there is a pair of words called the same number of repetitions that have not been explored more deeply by so many experts of Alqur'an. This study is a literature study in the form of descriptive qualitative research using approach 'Ulum al-Qur'a>n. This papar traces each pair of words that have the same number of repetitions in the Qur'an, the range of meanings of the repetitions in the Qur'an and than to further determines the munasabah (relation) between the pair of words. This study produces a table of pairs of words mentioned in the Qur'an with the same number, then produces a table of meaning ranges from those words in its repetition in the Qur'an which in turn gets some categories of linkages between the word pairs in the form of causal linkage, process-results, synonyms, antonyms, characters (characteristics), and functions. The results of this study are expected to bring up the other side of the miracles of the Qur'an from the point of the mufrada>t al-Qur'an. At the same time bring the hidden wisdom of the content of Alqur'an with the overall meaning and meaning of each Alqur'an word.